Impact of COVID-19 infection on pregnant women: literature review - Alasbi, Ghadah Mohammed; Saad, Afaf Mohammad; Abdulqader, Nada Jamal; Laimooniah, Sulaiman Hemdi; Aldajani, Fatimah Falah; Althowimer, Zaid Ali; Alduraywish, Ibrahim Sulaiman; Al raqi, Atheer Saeed; Alahmari, Ahmed Ali; Algethami, Amjaad Fahad; AlHumaid, Atheer Saleh; Alenezi, Ibtihaj Qaseem (International Journal Of Community Medicine And Public Health, 2021)
SARS-CoV-2 infection in high-risk groups is associated with high mortality and morbidity. Pregnant females are considered one of these cases. More studies are needed to understand how the virus affects the complication rate in these cases and what is the best management plan. Hence, this study was conducted to stand on the real incidence and complications of COVID-19 in pregnancy. Databases like PubMed, Medline, Web of science, Embase, Google scholar, and Scopus were searched using the following search terms “severe acute respiratory syndrome of coronavirus-2” or “SARS-CoV-2” or “COVID-19” or “coronavirus” and “pregnant” or “neonate” or “pregnancy” transplacental transmission” or “placental transmission” or “vertical transmission” or intrauterine or perinatal. Pregnant women are not considered high-risk groups for COVID-19 infections as it was found that the risk of complication in COVID-19 patients was similar to non-infected patients. However, virulent strains of the virus had caused severe infections and complications. The study lacked a clear plan for the management of the virus in pregnant females.